Cooperative routing in mobile ad hoc networks using fuzzy logic. (2017) - Venkanna, U.; Velusamy, R. Leela
Mobile ad hoc network (MANET), needs an unconditional cooperation among the nodes to communicate. Presence of malicious or selfish nodes in the routing path will affect the routing performance. In this paper, fuzzy logic based trust-AODV is proposed, which is an enhancement to the existing ad hoc on demand distance vector (AODV) protocol. The algorithm uses decision factors such as packet forwarding trust (PFT), energy level (EL), and time of availability (ToA) to decide the dynamic changing behaviour of a mobile node. Further, the decision factors are incorporated into Fuzzy logic model to calculate the Final Trust value of a mobile node which is used to establish a cooperative routing path. The simulated results are compared with AODV, dynamic source routing (DSR), TDSR and ad hoc on-demand trusted-path distance vector (AOTDV) algorithms with respect to routing parameters such as packet delivery ratio, average delay, routing packet overhead, and Energy consumption. The simulation results indicate that the proposed routing algorithm improves the routing performance.